Cause of death in adults with congenital heart disease — An analysis of the German National Register for Congenital Heart Defects. (15th May 2016) - Engelings, Claudia C.; Helm, Paul C.; Abdul-Khaliq, Hashim; Asfour, Boulos; Bauer, Ulrike M.M.; Baumgartner, Helmut; Kececioglu, Deniz; Körten, Marc-Andre; Diller, Gerhard-Paul; Tutarel, Oktay
Abstract: Background: Due to the great advances in the care of patients with congenital heart disease (CHD), mortality has decreased significantly over the last decades. Nonetheless, mortality for adults with congenital heart disease (ACHD) is still higher than for the general population. An analysis regarding causes of death in a nationwide contemporary cohort of ACHD is lacking. Methods: A well-characterized cohort of the German National Register for Congenital Heart Defects was screened for patients over the age of 18 years who died between January 2001 and January 2015. Data relating to the cardiac diagnosis, symptoms, operations, interventions, comorbidities, and causes of death were analyzed. Results: During a median follow-up of 3.67 years (IQR 1.32–9.41), 239 (9.2%) out of 2596 patients died during the study period (110 female (46%), mean age at death 39.8 ± 17.8 years). The majority of these deaths was CHD-related (171 patients (71.5%)). Leading causes of death were heart failure (n = 66, 27.6%), and sudden cardiac death (n = 55, 23.0%). Deceased patients had a more complex CHD and more extracardiac comorbidities compared with living patients. Conclusions: Causes of death of ACHD patients in a large contemporary cohort from a national register are in the majority still CHD-related, with heart failure being the leading cause of death. Additionally, extracardiac comorbidities gain increasing importance.